2020
DOI: 10.15174/au.2020.2892
|View full text |Cite
|
Sign up to set email alerts
|

Chemical proximate composition, antinutritional factors content, and antioxidant capacity of anatomical seed fractions of Moringa oleifera

Abstract: For rational use of moringa seeds and its anatomical fractions (kernel, shells, and wings), the objective of the present investigation was to analyze their chemical composition, antinutritional factors content, and antioxidant capacity. The seed kernel fraction represents 71.78% of the whole seed weight and possesses high contents of protein (32.19%) and lipids (38.72%), whereas seed shells and wings fractions are mainly composed of dietary fiber and carbohydrates. Phytate was the most abundant antinutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…On the other hand, the kernel has high protein, carbohydrate, and lipid content, significantly different (p < 0 05) from the shell. León-López et al [26] also showed a significant difference in composition between the shell and kernel of Moringa oleifera seeds.…”
Section: Resultsmentioning
confidence: 90%
“…On the other hand, the kernel has high protein, carbohydrate, and lipid content, significantly different (p < 0 05) from the shell. León-López et al [26] also showed a significant difference in composition between the shell and kernel of Moringa oleifera seeds.…”
Section: Resultsmentioning
confidence: 90%